Evaluation of the potential of the green tide macroalgae Chaetomorpha valida as a food source for Apostichopus japonicus. (13th September 2021) - Xing, Ronglian; Hu, Shujun; Wang, Lei; Shi, Kai; Chen, Lihong
Abstract: The potential of the green tide macroalgae Chaetomorpha valida as a food source for Apostichopus japonicus was evaluated in this study as a solution to ease the shortage of macroalgae. Four diets were formulated and tested with juvenile A .  japonicus in a laboratory simulation experiment for 6 weeks. Diets included commercial feed, Sargassum muticum, C .  valida and C .  valida fermentation feed. The crude protein content of the C .  valida fermentation feed was similar to that of the commercial feed, and its crude fat was comparable to S .  muticum . Though the energy intake of A .  japonicus in the fermentation feed group was the lowest, it accounted for the highest proportion of energy for growth. The growth rate of animals fed with fermentation feed was lower than those fed commercial feed, similar to S .  muticum feed, and consistent with the feed conversion efficiency for each diet. The contents of chemical oxygen demand (COD) and ammonia nitrogen of water in the fermentation feed group were the lowest. Its content of nitrite nitrogen of water also remained at a low level throughout. Overall, the fermented C .  valida was a useful alternative food source of S .  muticum for A .  japonicus aquaculture.